2009
DOI: 10.1007/s11665-009-9508-5
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of CrN/AlN Films Produced by Reactive Magnetron Sputtering

Abstract: The microstructure of CrN/AlN films, prepared by reactive magnetron sputtering under various conditions, was analyzed and related to the wear behavior of the films. One set of films was prepared by conventional reactive magnetron sputtering, a second set adding an extra amount of reactive gas to the initial Ar + N 2 mixture and a third set adding an extra source of nitrogen near the substrate during sputtering. The samples were analyzed by scanning electron microscopy + energy dispersive microanalysis, high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The latter is due to the formation of a dense chemically stable oxide scale, which retards further oxidation by suppressing the supply of oxide-forming metallic elements [ 2 , 5 ]. Coatings composed of alternating AlN/CrN layers show further enhancement of mechanical properties as compared to the CrAlN system [ 6 9 ]. Additionally, an improved oxidation resistance was observed in particular for AlN/CrN superlattice coatings with bilayer periods ≤4 nm [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is due to the formation of a dense chemically stable oxide scale, which retards further oxidation by suppressing the supply of oxide-forming metallic elements [ 2 , 5 ]. Coatings composed of alternating AlN/CrN layers show further enhancement of mechanical properties as compared to the CrAlN system [ 6 9 ]. Additionally, an improved oxidation resistance was observed in particular for AlN/CrN superlattice coatings with bilayer periods ≤4 nm [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional DC magnetron sputtering produced low metal ionization rate and poor film quality, which can not meet the requirements of new parts or devices. Therefore, how to improve the quality of the film is very important, some studies found that a certain amount of heat and energy in the surface of the film growth could improve the quality of the film [3,4], such as the substrate heating, a negative bias [5] and increasing the degree of ionization [6] and so on.…”
Section: Introductionmentioning
confidence: 99%